The Portuguese "novo cinema" and the Brazilian "cinema novo": the Glauber case - Cunha, Paulo (2018)
This short text intends to make an approximation between the Portuguese "novo cinema" and the Brazilian "cinema novo" from the bridges established by the Brazilian filmmaker Glauber Rocha with several Portuguese filmmakers. Knowing that, from the mid-1960s until his death, Glauber Rocha maintained a friendship and cinematic complicity with various figures of the Portuguese "novo cinema", I want to know if the Brazilian filmmaker would have been a fundamental element in the dialogue between the Brazilian and Portuguese cinemas in that period.